Filmmaking with biology undergraduates: combining digital technology with authentic assessment to develop students’ skillset and capabilities for life after graduation - A. Wakefield; R. R. Murray; E. Bell (Cogent Education, 2024)
AbstractThe use of technology in Higher Education teaching is now commonplace and can have multiple benefits for learners; however, the benefits of learner-generated digital media (LGDM) are understudied. Using a combination of pre- and post-workshop questionnaires and student critical reflections, we evaluated the impact of an assessed week-long filmmaking unit on preparing students for life after university. Quantitative results show a boost in student confidence in the areas of academic skills, teamwork, communication, and digital capabilities. We categorise our qualitative data in six main themes: self-confidence; emotional awareness; connecting and communicating; self-regulated learning; students as researchers; and authentic learning. Our findings suggest that students independently recognise the authenticity of team-based LGDM projects, understanding how it will prepare them for life after university. We discuss the value team-based filmmaking projects can have in developing student skills and competencies (both digital and human) and relate this to recent literature on authentic assessment and technology enhanced learning.